Shared interactions of six neurotropic viruses with 38 human proteins: a computational and literature-based exploration of viral interactions and hijacking of human proteins in neuropsychiatric disorders - Elif Asli Ozer; Aleyna Keskin; Yusuf Huseyin Berrak; Fatma Cankara; Fusun Can; Yasemin Gursoy-Ozdemir; Ozlem Keskin; Attila Gursoy; Hale Yapici-Eser (Discover Mental Health)
Abstract Introduction Viral infections may disrupt the structural and functional integrity of the nervous system, leading to acute conditions such as encephalitis, and neuropsychiatric conditions as mood disorders, schizophrenia, and neurodegenerative diseases. Investigating viral interactions of human proteins may reveal mechanisms underlying these effects and offer insights for therapeutic interventions. This study explores molecular interactions of virus and human proteins that may be related to neuropsychiatric disorders. Methods Herpes Simplex Virus-1 (HSV-1), Cytomegalovirus (CMV), Epstein-Barr Virus (EBV), Influenza A virus (IAV) (H1N1, H5N1), and Human Immunodeficiency Virus (HIV1&2) were selected as key viruses. Protein structures for each virus were accessed from the Protein Data Bank and analyzed using the HMI-Pred web server to detect interface mimicry between viral and human proteins. The PANTHER classification system was used to categorize viral-human protein interactions based on function and cellular localization. Results Energetically favorable viral-human protein interactions were identified for HSV-1 (467), CMV (514), EBV (495), H1N1 (3331), H5N1 (3533), and HIV 1&2 (62425). Besides immune and apoptosis-related pathways, key neurodegenerative pathways, including those associated with Parkinson’s and Huntington’s diseases, were frequently interacted. A total of 38 human proteins, including calmodulin 2, Ras-related botulinum toxin substrate 1 (Rac1), PDGF-β, and vimentin, were found to interact with all six viruses. Conclusion The study indicates a substantial number of energetically favorable interactions between human proteins and selected viral proteins, underscoring the complexity and breadth of viral strategies to hijack host cellular mechanisms. Further in vivo and in vitro validation is required to understand the implications of these interactions.